Overview of Current Research on Wolves in Russia - Poyarkov, Andrey D.; Korablev, Miroslav P.; Bragina, Eugenia; Hernandez-Blanco, Jose Antonio (Frontiers in Ecology and Evolution, 2022)
This paper provides an overview of wolf research in Russia at the beginning of the 21st century. Wolf research covered various directions, including population density estimation, management methods and minimization of human-wildlife conflicts, general and behavioral ecology, behavior, wolf population genetics and morphology, paleontology, dog domestication, helminthology and the wolves’ role in the rabies transmission. Some studies are performed with state-of-art methodology using molecular genetics, mathematical modeling, camera traps, and GPS telemetry